THE APPLICATION OF MENU ENGINEERING TECHNIQUE IN DETERMINING MARKETING STRATEGY AT THE DEN OF KALAHA RESTAURANT JAKARTA - Ardiansyah, Imam (APPS Publications, 2020)
The purpose of this research is to provide an overview of the decision to develop a strategy based on the results of menu sales that have occurred within a certain time frame. Evaluate menus to determine marketing strategies using menu engineering techniques. This type of research is a qualitative descriptive study that the object of this study is all food menus that are in the restaurant of The Den of Kalaha which were sold in the period July - December 2019. The results of the study were obtained from the evaluation of the July - Deember 2019 food menu at The Den of Kalaha Jakarta restaurants in all categories, there are 74 menu items in The Den of Kalaha Restaurant Jakarta, 14 items fall into the stars group or 18.91%. The plowhorses group is 22 or 29.72%. The puzzles group is 22 or 29.72%. While the group of dogs numbered 16 or 21.62%. Suggestions for management is to periodically implement the menu engineering technique, where the benefits are that management can be responsive and able to make the right decisions if profits having a decline.